2002
DOI: 10.1101/gad.230302
|View full text |Cite
|
Sign up to set email alerts
|

Axin-mediated CKI phosphorylation of β-catenin at Ser 45: a molecular switch for the Wnt pathway

Abstract: The Wnt pathway controls numerous developmental processes via the ␤-catenin-TCF/LEF transcription complex. Deregulation of the pathway results in the aberrant accumulation of ␤-catenin in the nucleus, often leading to cancer. Normally, cytoplasmic ␤-catenin associates with APC and axin and is continuously phosphorylated by GSK-3␤, marking it for proteasomal degradation. Wnt signaling is considered to prevent GSK-3␤ from phosphorylating ␤-catenin, thus causing its stabilization. However, the Wnt mechanism of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
572
4
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 668 publications
(620 citation statements)
references
References 59 publications
25
572
4
7
Order By: Relevance
“…It has long been known that CK1 isoforms play crucial roles in the Wnt/β‐catenin signalling 28, 29, 30, 34, 35, 43, 44, 45, 46. In fact, early observations that overexpression of CK1 isoforms in Xenopus embryos caused axis duplication suggested a positive role for CK1 in Wnt signalling 47.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that CK1 isoforms play crucial roles in the Wnt/β‐catenin signalling 28, 29, 30, 34, 35, 43, 44, 45, 46. In fact, early observations that overexpression of CK1 isoforms in Xenopus embryos caused axis duplication suggested a positive role for CK1 in Wnt signalling 47.…”
Section: Discussionmentioning
confidence: 99%
“…1). In the absence of Wnt signaling, β-catenin is phosphorylated by the serine/threonine kinases, Casein Kinase [10][11][12] and GSK-3 [13]. The interaction between these kinases and β-catenin is facilitated by the scaffolding proteins, Axin and APC [14,15].…”
Section: Wnt Signaling Within the Cellmentioning
confidence: 99%
“…4). Upon phosphorylation of ␤-catenin by the serine/threonine glycogen synthase kinase 3␤ (GSK3␤) and by casein kinase I, ␤-catenin gets ubiquitylated by the E3 ligase ␤-TRCP and degraded by the proteasome (Amit et al, 2002;Polakis, 2000Polakis, , 2012. Mutations in ␤-catenin which prevent its phosphorylation and subsequent ubiquitylation, and which result in a constitutive active transcription factor are found with significant frequency in HCC and it was shown that ␤-catenin plays a key role in the metastasis of human hepatocellular carcinoma (de La Coste et al, 1998;Lai et al, 2011).…”
Section: ˇ-Cateninmentioning
confidence: 99%